Impact of Social Media Use on Public Behavior Regarding COVID-19 Vaccination Refusal - Juliadi, Rismi; Angelia, Chininta Rizka; Faramita, Aazelia (UI Scholars Hub, 2025)
This study explores the impact of social media use on the behavior related to the refusal of the COVID-19 vaccination. Social media has been one of the most widely used sources of information during the COVID-19 pandemic. It provides easy access to a wide range of content, including information about the COVID-19 vaccination campaign carried out by the Indonesian government. However, content shared via social media is vulnerable to disinformation, fake news, and hoaxes. The use of social media during the pandemic has had a significant impact on people's attitudes toward vaccination, with vaccine hesitancy often stemming from multiple factors. This study aims to measure the impact of social media usage on behavior related to COVID-19 vaccination refusal. The research is grounded in the Uses and Gratification Theory (UGT) and the Theory of Planned Behavior (TPB), and employs a quantitative-explanatory research method. Data were collected via a survey of 196 respondents from generation X and Y, selected using a purposive sampling technique. The data analysis was conducted using Structural Equation Modelling (SEM) - Partial Least Square (PLS). Among the respondents—62% females and 38% males—the majority reported receiving an invitation from the Ministry of Health to participate in the vaccination program. The findings reveal a significant and nuanced distinction among the variables of information seeking and status seeking. Notably, purpose-driven or interactive social media activities were not significant predictors of vaccine refusal. In contrast, social media use for entertainment purposes emerged as a strong and statistically significant predictor of vaccine refusal behavior. This key finding suggests that passive consumption of entertainment-oriented content—such as memes, viral videos, or influencer narratives—may influence vaccine attitudes more powerfully than overtly persuasive or informative content. It appears that such content can bypass the critical scrutiny applied during active information-seeking behavior, thereby making entertainment-based media a potent vector for misinformation and vaccine hesitancy. The implication of this study reveals that the “entertainment” motive is the only significant predictor of the refusal of the COVID-19 vaccination, indicating that purely informational or data-heavy campaigns are ineffective against entertainment-driven misinformation. Therefore, public health communication should evolve toward emotionally engaging, narrative-based, and entertainment-oriented strategies, leveraging influencers, storytelling, and positive framing to foster hope, responsibility, and pro-vaccine behavior.